Improving adherence to cholesterol lowering guidelines through an interactive digital tool. Issue 4 (29th December 2021) - Rashid, S; Suero-Abreu, G A; Tysarowki, M; Um, H; Zhang, Y; Shah, K; Douglas, A; Matassa, D
Abstract: Background: Statins are the cornerstone of primary and secondary prevention of atheroscleoric cardiovascular disease (ASCVD). Our previous retrospective analysis of 1042 consecutive patient encounters at a large urban academic institution found that one in five patients were not prescribed an appropriate statin therapy. These patients tended to be younger, of Black race, and met statin-eligibility solely via a 10-year ASCVD risk score ≥7.5%. Only one-third of patients had follow-up cholesterol levels ordered to monitor treatment efficacy. Purpose: To improve adherence to cholesterol guidelines at our academic institution. Methods: We implemented multiple interventions over a four-month period to support clinical decision making of guideline directed statin therapy: a) development of an online interactive tool, b) physician education on updated cholesterol guidelines and utilization of the tool, c) display of guideline summary in the workspace, and d) a documentation reminder in the electronic health record. We randomly selected encounter dates, from which 622 consecutive patient visits were analyzed. The primary outcome measures were: prescription rates of statins, documentation of a 10-year ASCVD risk score, and follow-up cholesterol levels ordered to monitor treatment efficacy. Results: Out of the 622 patients, 232 met statin indication. In this post-intervention group, statin prescriptions rates improved when compared to the pre-intervention group (90.5% vs 82.3%, p=0.006). Among the patients who met statin indication solely via a 10-year ASCVD risk score ≥7.5%, there was an increase in documentation of the calculated 10-year ASCVD risk score (72.3% vs 57.8%; p=0.039) and in statin prescription rate (90.8% vs 67.6%; p<0.001). In addition, there was an increase in follow-up cholesterol levels ordered in all patients included in our study who met statin indication (64.1% vs 33.3%; p<0.001). Conclusion: Our study showed higher rates of statin prescription, 10-year ASCVD risk score documentation, and treatment monitoring after multiple interventions, including an easily accessible online interactive tool, at a large urban academic institution. Funding Acknowledgement: Type of funding sources: None.